Decline or stability of obligate freshwater elasmobranchs following high fishing pressure - Lucifora, Luis Omar (2017)
Despite elasmobranchs are a predominantly marine taxon, several species of sharks and rays are regularly found in fresh water. Although there is ample evidence of declining elasmobranch populations around the world, this evidence comes exclusively from marine and euryhaline species; the ecology and conservation status of obligate freshwater elasmobranchs is far from being understood. River stingrays (Potamotrygoninae, 32 species) live exclusively in South American rivers and represent the overwhelming majority of freshwater elasmobranch diversity. Here, we present evidence of a decline in the abundance of river stingrays in the middle and lower Paraná River, an extensive wetland mosaic of approximately 35,000 km2. By taking advantage of a stingray manipulation procedure widespread among South American fishermen, we were able to estimate spatial differences in relative fishing pressure and found that the observed decline is related to fishing pressure. The highest fishing effort and lowest relative abundance occurred in areas where fisheries operate on the riverfloodplain. The lowest fishing effort and highest relative abundances occurred in areas where fisheries operate in the main channel. The only species with a stable trend was Potamotrygon motoro. This evidence confirms the long-presumed vulnerability of obligate freshwater elasmobranchs and suggests that some species, e.g. P. motoro, can be exploited sustainably. Our results also indicate that negative effects on freshwater elasmobranchs can be minimized by adjusting fishing grounds.